Analisis Sistem Agribisnis Nira Aren di Desa Sei Jernih, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - Alda Eliya; Nasirwan Nasirwan; Syahrina Zahara; Tiffany Aprilia (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
In Indonesia, sugar palm plants have high economic potential and are widespread in various regions, especially humid areas. The aim of this research is to determine the income of the palm sap management business in Sei Jernih village, Deli Serdang Regency. The research method used is field research with primary and secondary data collection. The research results show that the sap processing business in Sei Jernih Village generates quite a large income and the income cost ratio (R/C) shows that the business is feasible and profitable. Marketing is carried out through two channels: directly from farmers to consumers and through retailers/agents. The conclusion of this research is that the palm sap processing site in Sei Jernih village has good economic potential and is worthy of further management. This includes increased productivity, further training and education, and efficient business management. By implementing this proposal, it is hoped that the palm palm sap processing business can develop and provide further benefits to farmers and local communities.